The relations between motivational factors and behavioral intentions of medical health tourists - Sancar, Tekin (Afyon Kocatepe Üniversitesi)
This study aims to determine the relationships between medical health tourists' perceptions of motivational factors and their behavioral intentions. In addition, it is aimed to redesign the health investments made with the existing medical technology in accordance with the medical health tourism trends and to develop motivational resources in this application process. The population of the study consists of international patients who have received medical health tourism services from health facilities operating in the province of Istanbul and holding a health tourism facility authorization certificate and who were reached through social media channels (Twitter, Instagram). The sample group consisted of 400 international medical tourists reached through the social media addresses (Twitter, Instagram) of health facilities operating in Istanbul and holding a health tourism facility authorization certificate. The data were collected through online survey technique. The total number of questionnaires evaluated and used in data analysis is 400. Accordingly, the overall average score of the motivational factors of medical health tourists is 3.94±0.58; the highest sub-dimension is "price affordability (4.39±0.75)" and the lowest sub-dimension is country knowledge and awareness (2.67±0.96). At the same time, looking at the evaluations of medical health tourists regarding their behavioral intentions, the general average score of behavioral intention was found to be 4.45±0.73. Based on the results of confirmatory factor analysis, it was revealed that there is a positive relationship between medical health tourists' motivational factors and their behavioral intentions at a high level and that medical health tourists' attitudes regarding their perceptions of motivational factors have a highly significant and positive effect on their attitudes regarding their behavioral intentions. This research has demonstrated that motivational factors can affect how a medical tourist perceives the image of the healthcare provider in the host country. First of all, since medical health tourism, which adds positive value to the economy, is an important preference criterion to be included in strategic plans, it is recommended that the government develop an effective policy in this direction. In addition, health investments in Türkiye with existing medical technology should be supported and redesigned in line with medical health tourism trends.

Bu araştırma ile medikal sağlık turistlerinin motivasyonel faktörlere yönelik algıları ile davranışsal niyetleri arasındaki ilişkilerin tespit edilmesi amaçlanmıştır. Bunun yanı sıra mevcut tıp teknolojisi ile yapılmakta olan sağlık yatırımlarının medikal sağlık turizmi trendlerine uygun olarak yeniden tasarlanması ve bu uygulama sürecinde motivasyon kaynaklarının geliştirilmesi hedeflenmiştir. Araştırmanın evrenini İstanbul ilinde faaliyet gösteren ve sağlık turizmi tesis yetki belgesine sahip sağlık tesislerinden medikal sağlık turizmi hizmeti almış olan ve sosyal medya kanalıyla (Twitter, Instagram) ulaşılan uluslararası hastalar oluşturmaktadır. Örneklem grubunu ise İstanbul ilinde faaliyet gösteren ve sağlık turizmi tesis yetki belgesine sahip sağlık tesislerinin sosyal medya adreslerinden (Twitter, Instagram) ulaşılan 400 uluslararası medikal turist oluşturmuştur. Araştırmanın verileri Google formlar üzerinden oluşturulan online anket tekniği ile elde edilmiştir. Toplamda 400 adet anket üzerinden analizler yapılmıştır. Buna göre, medikal sağlık turistlerinin motivasyonel faktörlerinin genel ortalama puanı 3,94±0,58; en yüksek alt boyut "fiyat uygunluğu (4,39±0,75)", en düşük alt boyut ise ülke bilgisi ve farkındalığıdır (2,67±0,96). Aynı zamanda medikal sağlık turistlerinin davranışsal niyetlerine ilişkin değerlendirmelerine bakıldığında davranışsal niyet genel ortalama puanı 4,45±0,73 bulunmuştur. Doğrulayıcı faktör analizi sonuçlarına göre medikal sağlık turistlerinin motivasyonel faktörleri ile davranışsal niyetleri arasında yüksek düzey pozitif yönlü bir ilişki olduğu ve medikal sağlık turistlerinin motivasyonel faktörlerine yönelik algılarının, onların davranışsal niyetlerine yönelik tutumlarını istatistiksel olarak anlamlı düzeyde ve pozitif yönde etkilediği tespit edilmiştir. Bu araştırma, motivasyonel faktörlerin bir medikal sağlık turistinin ev sahibi ülkedeki bir sağlık hizmet sunucusunun imajını nasıl algıladığını etkileyebileceğini ortaya koymuştur. Öncelikle ekonomiye pozitif değer katan medikal sağlık turizminin stratejik planlarda yer alması önemli bir tercih kriteri olduğundan, bu yönde hükümetin etkin bir politika geliştirmesi önerilmektedir. Ayrıca Türkiye'de mevcut tıbbi teknoloji ile yapılmakta olan sağlık yatırımlarının desteklenmesi ve medikal sağlık turizmi trendlerine uygun olarak yeniden tasarlanması gerekmektedir.
Medikal sağlık turistlerinin motivasyonel faktörleri ile davranışsal niyetleri arasındaki ilişkiler
Keywords: Motivational Factors; Behavioral Intentions; Medical Health Tourists; Motivasyonel Faktörler; Davranışsal Niyetler; Medikal Sağlık Turistleri